Concept of Multiplicity of Time Forms in Economy - ZHELAEVA, Svetlana E.; SAKTOEV, Vladimir E.; OSODOEVA, Olga A.; BAZHENOVA, Valentina S.; MIKULCHINOVA, Elena A. (Journal of Advanced Research in Law and Economics, 2016)
The purpose of research is to justify the position of the multiplicity of time forms in economy. In result of application of the methodology of interdisciplinary interaction of the concept of multiplicity of time forms, the category of economic time was studied, which objectively reflects the most common temporal relations that arise between a human and the environment in the course of economic activity.